Stock Returns and Economic Value Added: The Mediating Role of Earnings Per Share – Predicting Firms’ Financial Performance in Financial Markets - Suryana, Asep; Rifa'i, Asep Achmad; Prakoso, Sugih; Zaky, Muhammad; Suaebah, Ebah (IJBLE Scientific Publications Community Inc., 2025)
The purpose of this study is to determine the relationship between Economic Value Added (EVA) and Stock Return (SR), and to test the mediation role of Earning Per Share (EPS). The research design adapts the ex post facto method. The research sample is the financial statements of three Indonesian Telecommunication Companies on the IDX, for 6 years during 2017-2022, with the purposive sampling technique selected. Data analysis using a panel data regression model, developed with an estimated path analysis model using EViews v.14, model selection using CEM, FEM and REM approaches through Chow test, Hausman test, and LM test. The feasibility test of the selected model with the determination coefficient, and the significance test of the effect at alpha 0.05, the mediation test with the Sobel test. The research findings show that CEM as a selected model in the path equation model, with the feasibility criteria of the model being met. EVA has a positive and significant effect on EPS. EVA has a positive and significant direct effect on SR. EPS also has a significant positive effect on SR. The evaluation of mediation pathway parameters concluded that there was an indirect effect through EPS. Where the mediation effect of EPS is at the level of strong predictive ability.